A Progressive Design of MANET Security Protocol for Reliable and Secure Communication - Patsariya, Mohan; Rajavat, Anand (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The Mobile Ad-hoc Network (MANET) is a popular small area network, and rapidly deployable technology. That can be used in various applications due to flexibility, mobility, and wireless communication ability for commercial, defence, and domestic purpose. But the communication units are constrained with the resources such as battery life and security. Therefore, in this paper, we are exploring the MANET for accomplishing a secure and efficient routing. The proposed work contributes in three fields (1) providing a review for MANET routing (2) introduced a node capability based routing (NC-AODV) for improving communication reliability which contains the node quality of service for providing a capable route. (3) Introduced a Trusted node capability based routing (TNC-AODV) technique which is tested on the three security threats namely Black-hole, wormhole, and DOS flooding attack. We can also involve more attacks by incorporating the features of the attack. The implementation of the proposed technique has been carried out using NS2 simulator. Additionally, the performance of the protocol in different scenarios has been presented. The experimental results demonstrate the trust based model providing the effective security against considered attacks. Additionally, the scheme is able to improve the communication reliability in terms of Packet Delivery Ratio (PDR), and throughput. Finally, the possible and feasible future extension of the work has also been proposed.